Bridging Economic Theory Models and the Cointegrated Vector Autoregressive Model - Niels Framroze Møller (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
Examples of simple economic theory models are analyzed as restrictions on the Cointegrated VAR (CVAR). This establishes a correspondence between basic economic concepts and the econometric concepts of the CVAR: The economic relations correspond to cointegrating vectors and exogeneity in the economic model is related to econometric concepts of exogeneity. The economic equilibrium corresponds to the so-called long-run value (Johansen 2005), the long-run impact matrix, C; captures the comparative statics and the exogenous variables are the common trends. The adjustment parameters of the CVAR are related to expectations formation, market clearing, nominal rigidities, etc. Finally, the general-partial equilibrium distinction is analyzed.
Keywords: C32; 330; Cointegrated VAR; unit root approximation; economic theory models; expectations; Hybrid New Keynesian Phillips Curve; general equilibrium; VAR-Modell; Kointegration; Unit Root Test; Wirtschaftsmodell; New-Keynesian Phillips Curve; Allgemeines Gleichgewicht; Theorie